Bacteria-Targeted Clindamycin Loaded Polymeric Nanoparticles: Effect of Surface Charge on Nanoparticle Adhesion to MRSA, Antibacterial Activity, and Wound Healing - Nurhasni Hasan; Jiafu Cao; Juho Lee; Shwe Phyu Hlaing; Murtada A. Oshi; Muhammad Naeem; Min-Hyo Ki; Bok Luel Lee; Yunjin Jung; Jin-Wook Yoo (MDPI AG, 2019)
Adhesion of nanoparticles (NPs) to the bacterial cell wall by modifying their physicochemical properties can improve the antibacterial activity of antibiotic. In this study, we prepared positively charged clindamycin-loaded poly (lactic-co-glycolic acid)-polyethylenimine (PLGA-PEI) nanoparticles (Cly/PPNPs) and negatively charged clindamycin-loaded PLGA NPs (Cly/PNPs) and investigated the effect of NP adhesion to bacteria on the treatment of methicillin-resistant Staphylococcus aureus (MRSA)-infected wounds. The Cly/PPNPs and Cly/PNPs were characterized according to particle size, polydispersity index, surface charge, and drug loading. Both Cly/PPNPs and Cly/PNPs exhibited sustained drug release over 2 days. The Cly/PPNPs bind to the MRSA surface, thereby enhancing bactericidal efficacy against MRSA compared with the Cly/PNPs. Furthermore, compared with other groups, Cly/PPNPs significantly accelerated the healing and re-epithelialization of wounds in a mouse model of a MRSA-infected wounds. We also found that both NPs are harmless to healthy fibroblast cells. Therefore, our results suggest that the Cly/PPNPs developed in this study improve the efficacy of clindamycin for the treatment of MRSA-infected wounds.